Adams vs. Jefferson : the tumultuous election of 1800 - Ferling, John E. (Pivotal moments in American history., 2004)
A history of the presidential campaign follows the clash between the two candidates, Adams and Jefferson, and their different visions of the future of America, the machinations that led to Jefferson's victory, and the repercussions of the campaign.